2016
DOI: 10.1016/j.ahj.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban compared with parenteral heparin and/or vitamin K antagonist in patients with nonvalvular atrial fibrillation undergoing cardioversion: Rationale and design of the EMANATE trial

Abstract: This first prospective cardioversion study of a novel anticoagulant in anticoagulation-naïve patients should influence clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
3
22
0
5
Order By: Relevance
“…The efficacy and safety of NOACs prior to cardioversion was further evaluated in three large prospective randomized trials: X‐VeRT (eXplore the efficacy and safety of once‐daily oral riVaroxaban for the prevention of caRdiovascular events in patients with non‐valvular aTrial fibrillation scheduled for cardioversion), ENSURE‐AF (EdoxabaN vs. warfarin in subjectS UndeRgoing cardiovErsion of Atrial Fibrillation), and more recently EMANATE (Eliquis evaluated in acute cardioversion coMpared to usuAl treatmeNts for AnTicoagulation in subjEcts with non‐valvular atrial fibrillation). These trials showed a comparable risk of periprocedural events for rivaroxaban, edoxaban, and apixaban, respectively, to warfarin for patients undergoing electrical cardioversion . None of these trials considered the presence of intracardiac thrombi.…”
supporting
confidence: 90%
“…The efficacy and safety of NOACs prior to cardioversion was further evaluated in three large prospective randomized trials: X‐VeRT (eXplore the efficacy and safety of once‐daily oral riVaroxaban for the prevention of caRdiovascular events in patients with non‐valvular aTrial fibrillation scheduled for cardioversion), ENSURE‐AF (EdoxabaN vs. warfarin in subjectS UndeRgoing cardiovErsion of Atrial Fibrillation), and more recently EMANATE (Eliquis evaluated in acute cardioversion coMpared to usuAl treatmeNts for AnTicoagulation in subjEcts with non‐valvular atrial fibrillation). These trials showed a comparable risk of periprocedural events for rivaroxaban, edoxaban, and apixaban, respectively, to warfarin for patients undergoing electrical cardioversion . None of these trials considered the presence of intracardiac thrombi.…”
supporting
confidence: 90%
“…Similar to previous studies, this post-hoc analysis does not have sufficient statistical power to find small differences in outcomes, however available data reporting very few peri-cardioversion adverse events with either apixaban or warfarin treatment are reassuring. Currently, a prospective RCT comparing apixaban with the standard care of warfarin in anticoagulation-naïve patients undergoing cardioversion is ongoing [13] and will provide further useful information.…”
Section: Apixaban In Patients Undergoing Cardioversionmentioning
confidence: 99%
“…50 Direct oral anticoagulants appear to be a safe and effective alternative to warfarin for anticoagulation in cardioversion; some studies suggest improved outcomes with DOAC use. 51 Guidelines that recommend warfarin over DOACs were published prior to the majority of the former data being published. 25 It is reasonable to use DOACs both peri-and postprocedurally in patients undergoing cardioversion.…”
Section: Anti Coag Ul Ati On In C Ardiover S Ion For Atrial Arrhy Tmentioning
confidence: 99%